2018
DOI: 10.4067/s0718-58392018000300429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary concentrate supplementation on enteric methane emissions and performance of late lactation dairy cows

Abstract: Dietary supplementation with concentrates is regarded as an effective strategy to decrease the intensity of methane (CH4) emissions, although it has rarely been evaluated in late lactation dairy cows. The aim of the present study was to investigate the effects of two levels of dietary concentrate supplementation on CH4 emissions and milk production and composition of dairy cows in late lactation. The study was conducted using 24 multiparous Holstein Friesian cows in late lactation (253 ± 18 d in milk), and had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Similarly, buffaloes fed with concentrate have been shown to have good BCS [63], while cattle fed bypass fat showed improved feed intake [64]. On the other hand, the addition of 4 kg/d to 8 kg/d of concentrates for five weeks was able to improve the body mass gain without changes in BCS of dairy cows [65], while another study revealed that additional bypass fat did not improve body weight gain and BCS [66]. The variation in results might be due to the feed, energy and protein sources, period of feeding trials, type of animals, breeds, and the age of animals [66].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, buffaloes fed with concentrate have been shown to have good BCS [63], while cattle fed bypass fat showed improved feed intake [64]. On the other hand, the addition of 4 kg/d to 8 kg/d of concentrates for five weeks was able to improve the body mass gain without changes in BCS of dairy cows [65], while another study revealed that additional bypass fat did not improve body weight gain and BCS [66]. The variation in results might be due to the feed, energy and protein sources, period of feeding trials, type of animals, breeds, and the age of animals [66].…”
Section: Discussionmentioning
confidence: 99%